Scientific and practical bases of concepts of service quality and efficiency in hotel business (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The article discusses quality as a fundamental factor in survival in the face of growing consumer demands and competition. According to the author, the features of quality management play a crucial role in the hotel industry, as well as in the work of the hotel service.